Fixed time competing risk model - Jakaitienė, Audronė (Lietuvos matematikos rinkinys, 2000)
The competing risks under multinomial regression logit model is analyzed. The algorithms and software are made for this model in order to get estimation of parameters. Calculations are made using data of Cardiology Institute about health of 45-60 years old men, which were collected from 1972 till 1977.